KOMBINASI CONTRACT RELAX STRETCHING DAN INFRA MERAH SAMA BAIKNYA DENGAN PEDAL EXERCISE UNDERCOMPRESSION DAN INFRA MERAH UNTUK MENURUNKAN NYERI OTOT BETIS PADA PEMBATIK CAP DI BUARAN PEKALONGAN - Irine Dwitasari Wulandari; Nyoman Adiputra; Sugijanto - (Sport and Fitness Journal, 2015)
The work attitude ofstampbatik workers in conductedtheir dailyworkin standingposition. Stands work attitudeina longtimewillmake theworkeralwaystryingto balancethe body thus causing the static load on the feet. Static muscle contraction in along timewill cause ashort age of muscle blood flow, which results in reduced energy exchangeand egress metabolic wastein the active muscles, thus causing fatigue and pain. Theprocessing volvesa lot of loading on static muscle is faster cause muscle complaints,and this affects of the ability and decrease in labor productivity result. The purposeforknowing whether combination of contract relax stretching and infrared are better todecrease calf muscle pain compared with pedal exercise under compression and infraredon the stamp batik workerin home industries Buaran Pekalongan. Types of experimentalresearch, with the randomized study design pre and post test control group design.Group-1 (n =14) subjectswho receivedpedal exercise under compressionandinfrared,whileGroup-2 (n=14) get contract relax stretching and infrared. Analysis ofthe datawiththePaired Sample t-Test design mean scoresin the calf muscle pain in group1beforetreatmentwas142,857 mmHg and after 6 times treatment be172,142 mmHg, p=0.000. While the scores of calf muscle pain in Group-2 before treatment was 142,857mmHg and after 6 times treatment be170,714 mmHg, p =0.000. DifferenttestgroupswithGroup1 and Group 2 with astatistical analysis of Independent Sample-tTest value of p=0,871 (p>0.05).The conclusions obtained were exercise programsofcontract relax stretchingand infrared with pedal exercise under compression and infrared together can decrease calf muscle pain on the stamp batik worker. There is nosignificant different between the turn combination of contract relax stretching andinfrared with pedal exercise under compression and infraredto decrease calf muscle painon the stamp batik worker.